PENGARUH ARANG DAN ASAP CAIR TERHADAP PERTUMBUHAN ANAKAN Gyrinops sp. - Gusmailina; Sri Komarayati; Heru S. Wibisono (BRIN Publishing, 2018)
In Indonesia, Gyrinops is one important genera of agarwood producing trees, which is relatively slow growth. Stimulant addition is one possible way to enhance agarwood tree growth by improving the physiology activity. This paper studies the effect of charcoal and liquid smoke addition into the Gyrinops sp. seedling growth. Wood charcoal at various portion of 10%, 20% and 30%, and liquid smoke of 1%, 2%, 3% and 4% were added separately into seedling media. The charcoal and liquid smoke were made from mixed wood waste of sengon (Falcataria moluccana) and rubber wood (Hevea brasiliensis). Results showed that in general wood charcoal and liquid smoke addition improves Gyrinops seedling growth. The addition of 4% liquid smoke addition enhanced Gyrinops’s seedling growth as indicated by seedling height and diameter increments. In conclusion, wood charcoal and liquid smoke are two potential organic materials for seedling growth improvement.